Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Perawat di Rumah Sakit dalam Meningkatkan Kualitas Layanan Kesehatan - Ayu Anggraeni Dyah Purbasari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to systematically examine the influence of transformational leadership and organizational culture on nurses' performance in hospitals. The method used is a Systematic Literature Review (SLR) with a qualitative approach. The findings indicate that transformational leadership has a significant impact on improving nurses’ performance, particularly through enhanced work motivation, job satisfaction, loyalty, and team effectiveness. Transformational leaders inspire nurses by providing a vision, encouraging innovation, and fostering a supportive environment that aligns with their values and goals. As a result, nurses exhibit increased commitment to their work, higher engagement levels, and a proactive attitude toward their tasks, leading to better overall performance. Organizational culture also plays a crucial role, especially values such as collaboration, human orientation, and integrity, which have been shown to support a positive work environment and nurse productivity. A culture that prioritizes teamwork, shared responsibility, and mutual respect enables nurses to work more cohesively and efficiently. Hospitals with a supportive and inclusive culture experience reduced turnover rates and higher job satisfaction, as nurses feel valued and respected within the organization. Additionally, when the culture encourages continuous learning and professional development, nurses are more likely to stay updated on best practices and provide high-quality care to patients. However, differences in findings across studies suggest the need for contextual understanding and consistent internalization of cultural values. Factors such as geographical location, hospital size, and leadership styles may influence the degree of impact that transformational leadership and organizational culture have on nurse performance. Therefore, it is essential to adapt leadership strategies and cultural initiatives to the unique needs and challenges of each healthcare setting.